Use of otolith strontium:calcium and zinc:calcium ratio as indicator of habitat of Percophis brasiliensis in the Southwestern Atlantic Ocean - Avigliano, Esteban (2015)
We evaluate the simultaneous use of Sr: Ca and Zn: Ca ratios of the sagitta otolith as a potential indicator of the habitat of Percophis brasiliensis along a latitudinal gradient in the southwestern Atlantic Ocean (34-42ºS and 51-67ºW), in order to reliably identify fish stocks. Fish were collected in three sampling sites: Argentine-Uruguayan Common Fishing Zone (AUCFZ), El Rincón (ER) and San Matías Gulf (SMG). The otolith Sr:Ca and Zn:Ca ratios were determined by ICP-OES and EDTA volumetric method. The otolith Sr:Ca ratio was similar in the three sampling sites, while the Zn:Ca ratio was significantly higher in AUCFZ than in ER and SMG for all age groups. The discriminant analysis showed an association between the otolith Sr:Ca and Zn:Ca ratios from ER and SMG. Present results suggest the potential occurrence of two fish stocks of P. brasiliensis in the study area.